2017
DOI: 10.1111/nyas.13466
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol and cancer treatment: updates

Abstract: Cancer, a growing health problem worldwide, affects millions of people every year. The overall survival rates of most cancers have been prolonged owing to the efforts of clinicians and scientists. However, some tumors develop resistance to chemoradiotherapeutic agents, and the cancer research community continues to search for effective sensitizers. Resveratrol, a natural polyphenolic phytoalexin, has shown promising effects in inhibiting proliferation and cancer progression in several tumor models. However, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(74 citation statements)
references
References 73 publications
0
74
0
Order By: Relevance
“…Resveratrol-loaded nanoparticles have also demonstrated antioxidant potential in cancer cells [ 37 ]. In addition, resveratrol beneficial effects are also present when adopted as a conventional treatment support to cancer, using chemotherapy and radiotherapy [ 70 , 71 , 72 ]. Based on previous experimental and clinical trials, and on molecular characteristics of resveratrol, it could be used as: (i) A neoadjuvant chemotherapy agent before surgery to decrease tumor volume, owing to its ability to inhibit cancer cell proliferation and to induce apoptosis; (ii) an adjuvant chemotherapy drug to inhibit early cancer invasion and metastasis after surgery; (iii) a radiotherapy or chemotherapy sensitization agent in combination with chemotherapy agents, like capsaicin, docetaxel, doxorubicin, gemcitabine and temozolomide, since resveratrol may improve their anticancer effects; (iv) in cancer prevention for people under high risk of cancer; (v) a radioprotective agent to reduce treatment adverse effects, including radiotherapy-induced xerostomia and mucositis.…”
Section: Biological Activities Of Resveratrolmentioning
confidence: 99%
“…Resveratrol-loaded nanoparticles have also demonstrated antioxidant potential in cancer cells [ 37 ]. In addition, resveratrol beneficial effects are also present when adopted as a conventional treatment support to cancer, using chemotherapy and radiotherapy [ 70 , 71 , 72 ]. Based on previous experimental and clinical trials, and on molecular characteristics of resveratrol, it could be used as: (i) A neoadjuvant chemotherapy agent before surgery to decrease tumor volume, owing to its ability to inhibit cancer cell proliferation and to induce apoptosis; (ii) an adjuvant chemotherapy drug to inhibit early cancer invasion and metastasis after surgery; (iii) a radiotherapy or chemotherapy sensitization agent in combination with chemotherapy agents, like capsaicin, docetaxel, doxorubicin, gemcitabine and temozolomide, since resveratrol may improve their anticancer effects; (iv) in cancer prevention for people under high risk of cancer; (v) a radioprotective agent to reduce treatment adverse effects, including radiotherapy-induced xerostomia and mucositis.…”
Section: Biological Activities Of Resveratrolmentioning
confidence: 99%
“…14 A large number of studies have shown that resveratrol inhibits the initiation and progression of various tumors including breast cancer, prostate cancer, ovarian cancer, liver cancer, and lung cancer. 15,16 As a plant extract, clinical studies showed that resveratrol consumed at 5 g per day for 14 days in colon cancer patients with liver metastasis had no obvious side effects. In healthy people, 4 g a day of resveratrol for 14 days is tolerable.…”
Section: Introductionmentioning
confidence: 99%
“…RSV possesses a wide range of preventive and therapeutic options against different types of cancer [ 114 ] through its proapoptotic, antiproliferative and anti-inflammatory actions [ 115 , 116 ]. RSV also suppresses the malignant biologic behaviors of cancer cells, including proliferation, antiapoptosis, invasion, migration, EMT progress, levels of ROS and stemness [ 117 ]. Recently, RSV is proved be chemopreventive from tumorigenesis by targeting Sirt1 and suppression of NF-κB activation [ 118 ].…”
Section: Rsv With Strong Anti-carcinogenic Effect Via Cardiovasculmentioning
confidence: 99%